2022
DOI: 10.1186/s13014-022-02076-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of stereotactic body radiation in the enhancement of the quality of life in locally advanced pancreatic adenocarcinoma: a systematic review

Abstract: Introduction Up to 30% of pancreatic cancer patients initially present locally advanced (LAPC). Stereotactic body radiation therapy (SBRT) may be an additional palliative treatment option when curative resection is no longer achievable. Our systematic review aimed to assess the effect of SBRT on the quality of life in LAPC. Methods We searched five databases until June 29th, 2021, for original articles that reported on SBRT for histologically prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…And that the almost identical time to local progression could probably be due to the overlapping values of the biologically effective doses used in those two groups. Stereotactic radiotherapy given in short duration regimens may have a useful role to play in ensuring local control among patients with locally advanced pancreatic cancer with a more favorable prognoses, or even in elderly patients and those with a more tenuous performance status, so long as the treatment goals and acceptable risks are aligned between the patient and their care teams [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…And that the almost identical time to local progression could probably be due to the overlapping values of the biologically effective doses used in those two groups. Stereotactic radiotherapy given in short duration regimens may have a useful role to play in ensuring local control among patients with locally advanced pancreatic cancer with a more favorable prognoses, or even in elderly patients and those with a more tenuous performance status, so long as the treatment goals and acceptable risks are aligned between the patient and their care teams [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in QoL with non-ablative SBRT are often due to better pain control, reduced biliary complications, better nutritional status, and reduced nausea. 36 Ryan et al 37 reported that SBRT (median dose of 28 Gy in 5 fractions) for an inoperable elderly population resulted in significant QoL improvements. SBRT provided symptom palliation of pain, fatigue, anorexia, weight loss, and nausea in 73%, 20%, 58%, 80%, and 100%, respectively, within 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…This review analyzed 11 studies with 292 patients treated using 3-6 fractions with a dose of 4-15 Gy per fraction, and 73% of the patients underwent chemotherapy prior to radiotherapy. The authors observed significant improvement in pain, weight loss, and nausea [ 7 ].…”
Section: Discussionmentioning
confidence: 99%